INTEGRATIVE STRATEGIES IN A COMPETITIVE AND UNSTABLE BUSINESS ENVIRONMENT IN NIGERIA - Macaulay Enyindah Wegwu (Scholar Express Journal, 2022)
The study examined the relationship between integrative strategies and competitiveness of SMEs in Port Harcourt, Nigeria. The cross-sectional study posited research question and hypothesis which guided the collection of data. The population of the study consisted of 75 employees from 5 selected small and medium enterprises in Port Harcourt. The sampling method adopted was the convenience technique. The sample size was determined with the use of Krejcie and Morgan table. Sources of data was through primary sources. Data was analysed using descriptive and inferential statistics. The Spearman Rank Order Correlation Coefficient was used to test the hypothesis. Findings from the study revealed a positive and significant relationship between integrative strategies and competitiveness of small and medium enterprises in Port Harcourt. From the findings, the study concluded that firms that employ integrative strategies are more competitively advantageous than others without the strategies. Based on the findings of the study, the paper recommended that firms that wants to enjoy competitive edge over rivals should employ integrative strategies that will give them higher competitive advantages because of the stiff competition that exist in the business space.
Keywords: Business environment in Nigeria; Competitiveness; Integrative strategy